Detection of Prostate Cancer and Benign Prostatic Hyperplasia Using Prostate-Specific Antigen Testing: A Review of Clinical Research Studies (Journal of Bio-Science, 2024)
The most often diagnosed diseases in males, prostate cancer (Ca-P) is now the third most common malignancy to cause mortality in different countries of the world. Data showed that serum PSA and prostate volume were demonstrated a substantial log-linear association with age. Numerous studies have demonstrated that the level of fPSA and the ratio of fPSA/total PSA can distinguish between benign and malignant prostatic diseases, with much lower levels in patients with prostate cancer. In a group of 681 LUTS patients, researcher assessed total PSA, fPSA, and prostate volume. The prostate volume significantly correlated with both total serum PSA and free PSA, with r = 0.51 (p